Preparation method of safe slurry, safe slurry and safe coating structure for battery
Through multiple predispersion and stir dispersion steps, the problem of poor dispersion effect of ceramic materials in battery safety coating is solved, the uniform distribution of ceramic particles and the performance of safety coating are achieved, and the safety performance and service life of the battery are enhanced. .
Patent Information
- Application Number
- CN202411177212.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The prior art small and medium-sized ceramic materials have poor dispersion effects in battery safety coatings, resulting in poor energy density loss, adhesion, electrical conductivity and mechanical strength of the coating, affecting battery safety performance.
By adopting multiple predispersion and stir dispersion steps, the particle size and specific surface area of the ceramic material are controlled by adding dispersant and conductive agent in batches, ensuring uniform dispersion of ceramic particles in the slurry, and improving the stability and performance of the slurry.
The uniform distribution of ceramic particles is achieved, the adhesion, conductivity and mechanical strength of the safety coating are enhanced, the defects and voids of the coating are reduced, and the safety performance and service life of the battery are improved.
Smart Images

Figure CN119297185A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a safety slurry and a safety slurry and a safety coating structure for a battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high discharge platform, long cycle life, and no memory effect. They have been widely used in mobile phones, cameras, laptops, and other fields, as well as in power battery fields such as electric bicycles and electric vehicles. As one of the main components of lithium batteries, the safety performance of the pole piece is a key factor to be considered when designing the battery. Coating the pole piece with battery safety coating is a common method in the battery industry to improve battery safety performance.
[0003] The mixing method of battery safety slurry in the prior art is to mix each component in a certain proportion at the same time. Since the speed setting is related to the density difference between the solid and liquid phases, the liquid phase density, the solid phase concentration, the liquid phase viscosity, the particle size and other physical properties, the prior art is prone to agglomeration when dispersing small-particle ceramic materials, resulting in poor final dispersion effect.
[0004] The dispersion uniformity and stability of the slurry have a significant impact on the coating effect. The smaller the particle size of the ceramic material, the easier it is to agglomerate, and the existing dispersion method has a poor dispersion effect on small-particle ceramic materials. Therefore, the existing battery safety coating uses ceramic materials with larger particle sizes for the uniformity of slurry dispersion, but ceramic materials with larger particle sizes will not only cause a loss in battery energy density, but also affect the adhesion, conductivity and mechanical strength of the safety coating, thereby affecting the safety performance of the battery.
[0005] Based on this, it is urgent to invent a method for preparing a safe slurry to solve the above-mentioned technical problems. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing a safe slurry in view of the deficiencies of the prior art. The method for preparing a safe slurry can achieve uniform diffusion of ceramic materials and has a good dispersion effect in each step.
[0007] In order to solve the above technical problems, the present application adopts the following technical solution: a method for preparing a safe slurry is provided, comprising the following steps:
[0008] S1, adding 80 to 95 parts by weight of ceramic material and 120 to 200 parts by weight of solvent into a stirring tank, pre-stirring, achieving a first pre-dispersion, and obtaining a mixed solution I;
[0009] S2, adding 0.01 to 5 parts of a dispersant to the mixed solution I in step S1, pre-stirring, achieving a second pre-dispersion, and obtaining a mixed solution II;
[0010] S3, adding 1 to 5 parts of a conductive agent to the mixed solution II in step S2, pre-stirring, achieving a third pre-dispersion, and obtaining a mixed solution III, and stirring and dispersing the mixed solution III;
[0011] S4, adding 2 to 10 parts of a binder to the mixed solution III in step S3, pre-stirring, and performing a fourth pre-dispersion to obtain a mixed solution IV, and stirring and dispersing the mixed solution IV;
[0012] S5, adding 0.01 to 5 parts of a dispersant to the mixed solution IV in step S4 and stirring and dispersing the mixture to obtain a mixed solution V;
[0013] S6, slowly stirring and dispersing the mixed solution V in step S5 and reversing and defoaming, and finally slowly stirring and discharging the material to obtain a safe slurry;
[0014] Among them, the stirring temperature is 25℃±3℃.
[0015] The beneficial effects are: the preparation method of the safe slurry of the present application can ensure that the fine ceramic particles are evenly dispersed in the slurry, avoiding the phenomenon of particle agglomeration, thereby improving the overall performance and stability of the slurry, and through multiple pre-dispersion steps and stirring and dispersing, the particle aggregates can be more effectively broken up, and the interaction force between the particles can be reduced, thereby obtaining a more uniform particle distribution, which can effectively improve the dispersion effect of the ceramic particles, and the batch addition of the dispersant can ensure that the viscosity of the mixed liquid is appropriate. The mixed liquid has a good dispersion effect during stirring, ensuring that the slurry has excellent performance, and a reasonable dispersion and mixing process contributes to the mechanical strength, wear resistance and conductivity of the final slurry, thereby improving the actual application effect of the slurry, and the final defoaming step can remove the bubbles generated during the mixing process, ensure the uniformity and smoothness of the slurry, and reduce the defects of the subsequent coating process.
[0016] Specifically, the stirring linear speed of steps S1 to S5 is 9 to 15 m / s; the slow stirring dispersion revolution speed in step S6 is 10 to 30 rpm, the rotation speed is 0 rpm, and the time is 10 to 120 min; the slow stirring discharging revolution speed is 10 to 30 rpm, the rotation speed is 50 to 500 rpm, and the time is 10 to 120 min; the pre-stirring revolution speed in steps S1 to S4 is 10 to 20 rpm, and the stirring rotation speed is 2000 to 4000 rpm, wherein the stirring time of the pre-stirring in steps S1, S3 and S4 is 5 to 15 m in, the pre-stirring stirring time in step S2 is 20 to 40 min, the revolution speed of the stirring and dispersing in step S3 is 20 to 40 pm, the stirring rotation speed is 4000 to 5000 rpm, and the stirring time is 40 to 80 min; the revolution speed of the stirring and dispersing in step S4 is 20 to 40 pm, the stirring rotation speed is 4000 to 5000 rpm, and the stirring time is 180 to 250 min; the stirring revolution speed of the stirring and dispersing in step S5 is 20 to 40 rpm, the stirring rotation speed is 2000 to 4000 rpm, and the stirring time is 10 to 20 min.
[0017] Specifically, the dispersant in step S2 is a solute, specifically polyvinyl pyrrolidone, the dispersant in step S5 is a solvent, specifically isopropanol, and the solvent in step S1 is N-methylpyrrolidone.
[0018] Specifically, the solid content of the mixed solution obtained in steps S1 to S5 is between 20% and 40%.
[0019] Specifically, the ceramic material is at least one of boehmite and alumina, the binder is at least one of PVDF, SBR, PAA and CMC, the conductive agent is at least one of conductive carbon black, carbon nanotubes and graphene, and the dispersant is at least one of polyvinyl pyrrolidone and isopropyl alcohol.
[0020] The second object of the present invention is to provide a safe slurry prepared by the above-mentioned safe slurry preparation method, comprising the following components by weight: 80-95 parts of ceramic material, 2-10 parts of binder, 1-5 parts of conductive agent, and 0.01-5 parts of dispersant, wherein the particle size D10 of the ceramic material is 0.1-0.15 μm or greater than 0.3 μm, D50 is 0.1-2.5 μm, D90 is 0.5-5 μm, D99 is 1-10 μm, and the specific surface area is 1-40 m 2 / g.
[0021] The beneficial effects of the present invention are as follows: the present invention controls the particle size of the ceramic material so that the ceramic material can be well dispersed during the stirring and dispersing process, and the ceramic particles are more evenly distributed in the safety coating, reducing the gaps and defects that may exist in the safety coating, thereby enhancing the adhesion between the safety coating structure for the battery and the active material and the current collector, and the increase in specific surface area increases the contact area between the ceramic material and the binder, which can improve the adhesion between the safety coating and the substrate, thereby enhancing the adhesion. Due to the smaller particle size, the conductive network is more continuous and dense, the conductive performance in the safety coating structure is more uniform, and no breakpoints will occur, and the smaller particles can fill the tiny pores and defects in the coating, increase the density and compactness of the coating, thereby improving the mechanical strength, and can prevent the safety coating from rupturing due to stress concentration during use, forming a uniform and tight safety coating, which can provide more comprehensive protection, more effectively disperse the impact force when subjected to force, reduce the possibility of rupture, reduce the risk of puncture or short circuit, and make the safety coating structure for the battery have better adhesion, conductivity and mechanical strength.
[0022] Specifically, the mass ratio of the binder to the conductive agent is (1-5):1.
[0023] The third object of the present invention is to provide a safety coating structure for a battery, which is formed by the above-mentioned safety slurry coated on both sides of the current collector in the thickness direction, including the above-mentioned safety coating coated on both sides of the current collector in the thickness direction, and the surface of the coating structure is also coated with an active material layer, and the area of the coating structure is greater than or equal to the area of the active material layer.
[0024] The beneficial effect is that by setting a battery safety coating structure on the surface of the current collector, the current collector and the active material of the battery are isolated. When the battery is punctured and short-circuited, the current on the active material needs to pass through the battery safety coating structure to reach the current collector, so that the battery safety coating structure is connected during the battery short circuit, which increases the resistance of the battery during the short circuit and prevents the battery from heating and catching fire after being punctured. In addition, the safety coating can avoid Al-Anode short circuit, greatly reducing the risk of battery smoke and fire.
[0025] Specifically, the bonding force formed between the safety coating structure and the current collector is greater than or equal to 400 N / m, the thickness of the safety coating structure is 1 to 5 μm, and the surface density is 7 mg / 1540.25 mm 2 ~10mg / 1540.25mm 2 .
[0026] Specifically, the film resistance of the safety coating structure is 0.2-3Ω. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0028] Figure 1 This is a schematic diagram of the process of Example 1 of the present application;
[0029] Figure 2 It is a top view of Example 3 of the present invention;
[0030] Figure 3 is a cross-sectional view of Example 3 of the present invention;
[0031] Figure 4 This is one of the microscopic morphology images of the cross section of the pole piece of Example 3 of the present invention;
[0032] Figure 5 This is the second microscopic morphology diagram of the cross section of the pole piece of Example 3 of the present invention.
[0033] Among them: 1-safety coating structure; 2-active material layer; 3-current collector. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0035] The following is combined with Figures 1 to 5 The present invention is further described in detail, but is not intended to limit the present invention.
[0036] The applicant found that in the prior art, the battery safety coating may crack or peel under mechanical stress or impact, and may not maintain good insulation or stability under high temperature conditions, resulting in a decrease in the safety performance of the battery when it suffers from short circuit or thermal runaway. This is because the battery safety coating has poor adhesion, and it is easy to fall off when impacted, causing the battery safety coating to fail, and the battery safety coating will expand at high temperatures, causing cracks in the battery safety coating and failing to maintain insulation performance. The above phenomenon is because the ceramic material used in the prior art has a large particle size, which is easy to cause stress concentration in the safety coating, reducing the adhesion between the safety coating and the current collector 3, making it easier to peel under impact, increasing the risk of crack generation, and the thermal expansion of larger particles at high temperatures may be uneven, causing cracks in the coating, affecting insulation and stability, and the use of ceramic materials with smaller particle sizes is prone to agglomeration, resulting in uneven dispersion of ceramic materials in the battery coating structure 1. The mixing method of battery safety coating in the prior art is to mix each component in a certain proportion at the same time, without considering that the speed setting is related to the density difference between the solid and liquid phases, the liquid phase density, the solid phase concentration, the liquid phase viscosity, the particle size and other physical properties. The prior art is prone to agglomeration when dispersing small-particle ceramic materials, and the dispersion effect is poor. Therefore, the applicant proposed an improved method for preparing safety slurry, by adding dispersants in batches to adjust the viscosity of the mixed liquid, and by controlling the stirring time and speed to control the shear effect of the fluid on the ceramic material, so that the stirring process maintains a good dispersion effect, controls the order of adding different components, and performs pre-dispersion and dispersion stirring multiple times, and adjusts the viscosity of the mixed liquid in each step to achieve full dispersion of each component.
[0037] Example 1
[0038] like Figure 1 As shown, the method for preparing the safety slurry of this embodiment comprises the following steps:
[0039] S1, adding 80 to 95 parts by weight of ceramic material and 120 to 200 parts by weight of solvent into a stirring tank, pre-stirring, achieving a first pre-dispersion, and obtaining a mixed solution I;
[0040] S2, adding 0.01 to 5 parts of a dispersant to the mixed solution I in step S1, pre-stirring, achieving a second pre-dispersion, and obtaining a mixed solution II;
[0041] S3, adding 1 to 5 parts of a conductive agent to the mixed solution II in step S2, pre-stirring, achieving a third pre-dispersion, and obtaining a mixed solution III, and stirring and dispersing the mixed solution III;
[0042] S4, adding 2 to 10 parts of a binder to the mixed solution III in step S3, pre-stirring, and performing a fourth pre-dispersion to obtain a mixed solution IV, and stirring and dispersing the mixed solution IV;
[0043] S5, adding 0.01 to 5 parts of a dispersant to the mixed solution IV in step S4 and stirring and dispersing the mixture to obtain a mixed solution V;
[0044] S6, slowly stirring and dispersing the mixed solution V in step S5 and reversing and defoaming, and finally slowly stirring and discharging the material to obtain a safe slurry;
[0045] Preliminary mixing of solid materials with liquid media through multiple pre-dispersion helps break up particle agglomerations, thereby reducing the energy and time required in the subsequent dispersion process.
[0046] Among them, the stirring temperature is 25℃±3℃.
[0047] By setting a reasonable stirring temperature, the mixed liquid can have good molecular diffusion ability and will not affect the mixing ability due to denaturation of different components caused by excessively high temperature.
[0048] Preferably, in steps S1 to S6, the solid content of the prepared mixed solution is between 20% and 40%, ensuring that the solid content is not too high and the solvent can wet the surface of the ceramic material, and the solid content is not too low, ensuring a better dispersion effect of the ceramic material.
[0049] Preferably, the stirring linear speed of steps S1 to S5 is 9 to 15 m / s; the present application controls the stirring linear speed within a certain range to prevent excessive stirring linear speed from causing excessive pressure on the mixed liquid, which may also increase frictional heat generation and affect the thermal stability of the material, and also has good stirring efficiency. When different radii of dispersion disks are selected for stirring, the rotation speed can be converted according to the linear speed and the radius of the dispersion disk.
[0050] Preferably, the present application uses a planetary stirring disperser, which is composed of a twist-shaped stirring paddle and a sawtooth lotus-shaped dispersion disk. Among them, the twist-shaped stirring paddle can make the slurry flow in a large range in the disperser, forming a stable flow field, which plays a role in modifying the surface of the material; the sawtooth lotus-shaped dispersion disk can rotate at high speed to form a high-speed flow field, which plays a role in dispersing shear. The radius of the dispersion disk can be selected according to Table 1, and selecting a dispersion disk with a suitable diameter can ensure the mixing effect.
[0051] Table 1
[0052]
[0053] In step S6, the slow stirring dispersion revolution speed is 10-30rpm, the rotation speed is 0rpm, and the time is 10-120min; the slow stirring discharging revolution speed is 10-30rpm, the rotation speed is 50-500rpm, and the time is 10-120min.
[0054] Preferably, the pre-stirring revolution speed in steps S1 to S4 is 10 to 20 rpm, and the stirring rotation speed is 2000 to 4000 rpm. The stirring time of pre-stirring in steps S1, S3 and S4 is 5 to 15 min. The pre-stirring stirring time in step S2 is 20 to 40 min. The revolution speed of stirring and dispersing in step S3 is 20 to 40 pm, the stirring rotation speed is 4000 to 5000 rpm, and the stirring time is 40 to 80 min. The revolution speed of stirring and dispersing in step S4 is 20 to 40 pm, the stirring rotation speed is 4000 to 5000 rpm, and the stirring time is 180 to 250 min. The stirring revolution speed of stirring and dispersing in step S5 is 20 to 40 rpm, the stirring rotation speed is 2000 to 4000 rpm, and the stirring time is 10 to 20 min.
[0055] Specifically, the dispersant in step S2 is a solute, specifically polyvinyl pyrrolidone, the dispersant in step S5 is a solvent, specifically isopropanol, and the solvent in step S1 is N-methylpyrrolidone.
[0056] Preferably, polyvinyl pyrrolidone and isopropanol are used together to achieve a better dispersion effect. Polyvinyl pyrrolidone is a polymer compound with polar groups (such as amino and carbonyl groups), which can interact with polar or charged groups on the surface of ceramic particles. This interaction helps the dispersant to adhere to the surface of the particles, forming a protective layer and reducing the mutual attraction between the particles. The addition of polyvinyl pyrrolidone can reduce the friction between the ceramic particles, making the particles easier to flow and disperse in the liquid. In addition, it also reduces the adhesion of particles to the surface of the equipment, improves the processing performance, and can adjust the viscosity of the mixed solution, so that the fluidity and uniformity of the slurry are optimized. Isopropanol has a strong solubility and a low surface tension. It can improve the wettability of the particles and make the particles easier to disperse in the solvent, which helps to break the agglomeration structure of the particles and make them evenly distributed. The combination of polyvinyl pyrrolidone and isopropanol can obtain a better dispersion effect. Polyvinyl pyrrolidone provides stability and a protective layer, and isopropanol improves wettability and adjusts viscosity.
[0057] The solvent is N-methylpyrrolidone and isopropyl alcohol. In the subsequent steps of preparing the safety coating structure 1, the safety slurry needs to be applied to the current collector and dried in an oven to form the safety coating structure 1. Isopropyl alcohol and N-methylpyrrolidone will evaporate into the air. Isopropyl alcohol only plays a role in helping the dispersion of the ceramic material during the stirring and dispersing process, and will not remain in the final safety coating structure 1 to prevent affecting the performance of the safety coating structure 1.
[0058] Preferably, the ceramic material is at least one of boehmite and alumina, the binder is at least one of PVDF, SBR, PAA and CMC, the conductive agent is at least one of conductive carbon black, carbon nanotubes and graphene, and the dispersant is at least one of polyvinyl pyrrolidone and isopropanol. The materials within the above range maintain good compatibility through the preparation method of the present application, reducing potential mixing problems.
[0059] Example 2
[0060] A safe slurry comprises the following components by weight: 80-95 parts of ceramic material, 2-10 parts of binder, 1-5 parts of conductive agent, and 0.01-5 parts of dispersant, wherein the particle size D10 of the ceramic material is 0.1-0.15 μm or greater than 0.3 μm, D50 is 0.1-2.5 μm, D90 is 0.5-5 μm, D99 is 1-10 μm, and the specific surface area is 1-40 m 2 / g.
[0061] Preferably, the mass ratio of the binder to the conductive agent is (1-5):1. Within this range, the battery safety coating structure 1 of the present application can form a conductive network structure. Since the conductivity of the binder is low and the bonding effect of the conductive agent is poor, when the content of the conductive agent is too much, the conductivity is improved and the bonding performance is reduced, and it is impossible to provide a suitable bonding strength. When the resistance is too small, it cannot provide sufficient insulation effect and cannot pass the needle puncture test 100%. When the content of the binder is too much, the bonding performance is improved and the conductivity is reduced, and a conductive network cannot be formed. The internal resistance of the battery is too large, and the capacity retention rate of the battery decays rapidly, greatly reducing the service life of the battery.
[0062] Example 3
[0063] like Figures 2 to 5 As shown, a safety coating structure 1 for a battery is formed by the above-mentioned safety slurry coated on both sides of the current collector 3 in the thickness direction, including the above-mentioned safety slurry coated on both sides of the current collector 3 in the thickness direction, and the surface of the safety coating structure 1 is also coated with an active material layer 2, and the area of the safety coating structure 1 is greater than or equal to the area of the active material layer 2.
[0064] Specifically, it includes 85% to 95% by mass of ceramic material, 2% to 10% of binder, 1% to 5% of conductive agent and 0.01% to 5% of dispersant.
[0065] In order to improve the adhesion of the safety coating for the battery, the present application uses a ceramic material with a specific particle size, which not only maintains the uniformity of the dispersion of the ceramic material but also ensures the adhesion of the safety coating structure 1 for the battery, improves the overall structural strength of the safety coating, and has good insulation properties at high temperatures, ensuring that the battery of the present application will not experience thermal runaway when punctured.
[0066] Preferably, the thickness of the safety coating structure 1 is 1-5 μm, and the surface density is 7 mg / 1540.25 mm 2 ~10mg / 1540.25mm 2 , the needle puncture pass rate can be improved by increasing the thickness, insulation effect and mechanical properties of the safety coating structure 1, but if the safety coating structure 1 is too thick, the energy density of the battery will be lost. When the thickness of the safety coating structure 1 of the present application is within the above range, the insulation and mechanical properties of the safety coating structure 1 can be guaranteed.
[0067] Preferably, the bonding force formed between the safety coating structure 1 and the current collector 3 is greater than or equal to 400 N / m. When the bonding force is within the above range, it can be ensured that the safety coating structure 1 and the current collector 3 do not peel off in the electrolyte environment. During acupuncture, the safety coating structure 1 and the current collector 3 do not peel off. At the same time, the safety coating structure 1 can prevent Al-Anode short circuit and avoid thermal runaway of the battery.
[0068] Preferably, the film resistance of the safety coating structure 1 is 0.2-3Ω. When the resistance of the safety coating structure 1 is within the above range, it can provide the necessary conductivity without affecting the insulation performance of the coating due to too low resistance.
[0069] Example 4
[0070] The method for preparing the safe slurry of this embodiment comprises the following steps:
[0071] The total stirring mass is 4.613Kg, the planetary stirring disperser is 5L, the dispersion plate radius is 24.92mm, and the dispersion plate morphology is sawtooth lotus. The circulating water is turned on throughout the process, and the stirring temperature is 25℃±3℃.
[0072] 1) Add 2.515 kg of N-methylpyrrolidone solution;
[0073] 2) Add particle size D10 greater than 0.3μm, D50 of 1.2-2.5μm, D90 < 5.0μm, D99 < 10μm, specific surface area of 2-6m 2 / g boehmite powder 1.3Kg;
[0074] 3) Pre-dispersion: orbital revolution 15 rpm, rotation 3620 rpm, time 10 min;
[0075] 4) Add 0.0014 kg of polyvinyl pyrrolidone powder as dispersant;
[0076] 5) Pre-dispersion: orbital revolution 15 rpm, rotation 3620 rpm, time 30 min;
[0077] 6) Add 0.0258 kg of conductive agent Super P powder;
[0078] 7) Pre-dispersion: orbital revolution 15 rpm, rotation 3620 rpm, time 10 min;
[0079] 8) Dispersion revolution 30rpm, rotation 4330rpm, time 60min;
[0080] 9) Add 0.8065 kg of PVDF glue with 7% solid content;
[0081] 10) Pre-dispersion: orbital revolution 15 rpm, rotation 3620 rpm, time 10 min;
[0082] 11) Dispersion revolution 30rpm, rotation 4330rpm, time 210min;
[0083] 12) Add 0.0645 kg of dispersant isopropanol solution;
[0084] 13) Dispersion revolution 30 rpm, rotation 3620 rpm, time 15 min;
[0085] 14) Stir slowly, orbital speed 20 rpm, rotation speed 0 rpm, time 30 min;
[0086] 15) Adjust viscosity and solid content, revolution 25 rpm, rotation 3620 rpm, time 20 min;
[0087] 16) Reverse defoaming, revolution 20 rpm, rotation 1200 rpm, time 30 min;
[0088] 16) Stir slowly to discharge the material, revolution 20rpm, rotation 200rpm, time 30min;
[0089] 17) Measure slurry viscosity, solid content and particle size.
[0090] Example 5
[0091] The difference from Example 4 is that in step 2, the boehmite powder selected is different, with a particle size D10>0.3μm, D50 of 0.5-1.4μm, D90≤3.0μm, D99≤5.0μm, and a specific surface area of 4-6m 2 / g;
[0092] The rest is the same as that of Example 4 and will not be described again here.
[0093] Example 6
[0094] The difference from Example 4 is that in step 2, the boehmite powder selected is different, with a particle size D10>0.1μm, D50 of 0.3-0.6μm, D90≤2.0μm, D99≤3.0μm, and a specific surface area of 8-16m 2 / g;
[0095] The rest is the same as that of Example 4 and will not be described again here.
[0096] Example 7
[0097] The difference from Example 4 is that in step 2, the boehmite powder selected is different, with a particle size of D10≤0.15μm, D50≤0.3μm, D90≤1.5μm, D99≤2μm, and a specific surface area of 18-32m 2 / g;
[0098] The rest is the same as that of Example 4 and will not be described again here.
[0099] Comparative Example 1
[0100] The difference from Example 4 is that in step 2, the boehmite powder selected is different, and its particle size D10 is 0.4 μm, D50 is 3.0 μm, D90 is 6.0 μm, and D99 is 12.0 μm;
[0101] The rest is the same as that of Example 4 and will not be described again here.
[0102] Comparative Example 2
[0103] The difference from Example 4 is that in step 2, the boehmite powder selected is different, and its particle size D10 is 0.8, D50 is 6.0 μm, D90 is 10.0 μm, and D99 is 20.0 μm;
[0104] The rest is the same as that of Example 4 and will not be described again here.
[0105] Adhesion testing of safety coatings
[0106] Test steps: stick the double-sided tape on the steel plate, use a cutting knife to cut the electrode coated with safety slurry, cut out a small square strip that is not much different from the size of the steel plate and stick it on the double-sided tape on the steel plate. After rolling it twice with a pressure wheel, measure the peeling force on the tensile tester. The test speed is 200mm / min.
[0107] Acupuncture test method
[0108] The electrode coated with the safety slurry is prepared into a battery and then subjected to a needle puncture test;
[0109] 1) At 23±2℃, place for 5 minutes; charge at 1C constant current to 4.2V; then charge at 0.7C constant current and constant voltage to 4.5V, with a cut-off current of 0.02C, and record the voltage, internal resistance, and thickness;
[0110] 2) The diameter of the steel needle is 4mm and the cone length of the steel needle is 14mm;
[0111] 3) Align the probe directly below the center, left side (7.5mm from the edge) and right side (7.5mm from the edge) of the largest surface of the battery cell, close and lock the explosion-proof cabinet, use a steel needle to completely pierce the battery cell at a speed of 40mm / s and do not pull out the needle for 10 minutes. When the surface temperature of the battery cell drops to 55℃, make a judgment and use a multi-channel thermometer to record the temperature rise.
[0112] Judgment criteria: no fire, no explosion, sparks from the pinholes inside the battery cell are acceptable.
[0113] The test results are shown in Table 2
[0114] Table 2
[0115]
[0116]
[0117] According to Examples 4 to 7 and Comparative Examples 1 to 2, it can be seen that when the particle size of the ceramic material is smaller, the bonding force is greater, and when the bonding force of the safety coating structure 1 is greater, the needle penetration rate is higher. This is because when the bonding force is large, the safety coating structure 1 is not easy to fall off due to external force, and its stability is good. In addition, since the particle size of the ceramic material is suitable, the compactness of the safety coating structure 1 is better, and the debris of the current collector 3 cannot pierce the safety coating structure 1, which has a better insulation effect.
[0118] The above description shows and describes several preferred embodiments of the present invention, but as before, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept of this article through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a safe slurry, characterized in that: The following steps are involved: S1, adding 80 to 95 parts by weight of ceramic material and 120 to 200 parts by weight of solvent into a stirring tank, pre-stirring, achieving a first pre-dispersion, and obtaining a mixed solution I; S2, adding 0.01 to 5 parts of a dispersant to the mixed solution I in step S1, pre-stirring, achieving a second pre-dispersion, and obtaining a mixed solution II; S3, adding 1 to 5 parts of a conductive agent to the mixed solution II in step S2, pre-stirring, achieving a third pre-dispersion, and obtaining a mixed solution III, and stirring and dispersing the mixed solution III; S4, adding 2 to 10 parts of a binder to the mixed solution III in step S3, pre-stirring, and performing a fourth pre-dispersion to obtain a mixed solution IV, and stirring and dispersing the mixed solution IV; S5, adding 0.01 to 5 parts of a dispersant to the mixed solution IV in step S4 and stirring and dispersing the mixture to obtain a mixed solution V; S6, slowly stirring and dispersing the mixed solution V in step S5 and reversing and defoaming, and finally slowly stirring and discharging the material to obtain a safe slurry; Among them, the stirring temperature is 25℃±3℃.
2. The method for preparing the safe slurry according to claim 1, characterized in that: The stirring linear speed of steps S1 to S5 is 9 to 15 m / s; the slow stirring dispersion revolution speed in step S6 is 10 to 30 rpm, the rotation speed is 0 rpm, and the time is 10 to 120 min; the slow stirring discharging revolution speed is 10 to 30 rpm, the rotation speed is 50 to 500 rpm, and the time is 10 to 120 min; the pre-stirring revolution speed in steps S1 to S4 is 10 to 20 rpm, and the stirring rotation speed is 2000 to 4000 rpm, wherein the stirring time of the pre-stirring in steps S1, S3 and S4 is 5 to 15 min The pre-stirring stirring time in step S2 is 20 to 40 minutes, the revolution speed of the stirring and dispersing in step S3 is 20 to 40 pm, the stirring rotation speed is 4000 to 5000 rpm, and the stirring time is 40 to 80 minutes; the revolution speed of the stirring and dispersing in step S4 is 20 to 40 pm, the stirring rotation speed is 4000 to 5000 rpm, and the stirring time is 180 to 250 minutes; the stirring revolution speed of the stirring and dispersing in step S5 is 20 to 40 rpm, the stirring rotation speed is 2000 to 4000 rpm, and the stirring time is 10 to 20 minutes.
3. The method for preparing the safe slurry according to claim 1, characterized in that: The dispersant in step S2 is a solute, specifically polyvinyl pyrrolidone, the dispersant in step S5 is a solvent, specifically isopropanol, and the solvent in step S1 is N-methylpyrrolidone.
4. The method for preparing the safe slurry according to claim 1, characterized in that: The solid content of the mixed solution obtained in steps S1 to S5 is between 20% and 40%.
5. The method for preparing the safe slurry according to claim 1, characterized in that: The ceramic material is at least one of boehmite and alumina, the binder is at least one of PVDF, SBR, PAA and CMC, the conductive agent is at least one of conductive carbon black, carbon nanotubes and graphene, and the dispersant is at least one of polyvinyl pyrrolidone and isopropyl alcohol.
6. A safety slurry prepared by the method for preparing a safety slurry according to any one of claims 1 to 5, characterized in that: The invention comprises the following components by weight: 80-95 parts of ceramic material, 2-10 parts of binder, 1-5 parts of conductive agent, and 0.01-5 parts of dispersant, wherein the particle size D10 of the ceramic material is 0.1-0.15 μm or greater than 0.3 μm, D50 is 0.1-2.5 μm, D90 is 0.5-5 μm, D99 is 1-10 μm, and the specific surface area is 1-40 m 2 / g.
7. The safety slurry according to claim 6, characterized in that: The mass ratio of the binder to the conductive agent is (1-5):
1.
8. A safety coating structure for a battery, characterized in that: It is formed by the safety slurry described in any one of claims 6 or 7 coated on both sides of the current collector (3) in the thickness direction, and the surface of the safety coating structure (1) is also coated with an active material layer (2), and the area of the safety coating structure (1) is greater than or equal to the area of the active material layer (2).
9. The safety coating structure for a battery as claimed in claim 8, characterized in that: The bonding force formed between the safety coating structure (1) and the current collector (3) is greater than or equal to 400 N / m, the thickness of the safety coating structure (1) is 1 to 5 μm, and the surface density is 7 mg / 1540.25 mm 2 ~10mg / 1540.25mm 2 .
10. The safety coating structure for a battery according to claim 8, characterized in that: The film resistance of the safety coating structure (1) is 0.2-3Ω.
Citation Information
Patent Citations
Preparation method of electrode slurry for flexible battery
CN111564632A
Lithium ion battery safety coating slurry and dispersion method thereof
CN113675378A
Method for producing slurry composition for secondary battery positive electrode, positive electrode for secondary battery produced using same, and lithium secondary battery comprising same
WO2018174619A1
Negative electrode pre-dispersion solution, negative electrode composition including same, negative electrode for lithium secondary battery including negative electrode composition, lithium secondary battery including negative electrode, and method for producing negative electrode composition
WO2023055216A1
Negative electrode slurry, preparation method therefor, negative electrode sheet, battery cell, battery, and electric device
WO2024021086A1